Uptake of dopamine and 5-hydroxytryptamine by platelets of patients with Parkinsonism. Issue 7 (July 1978) - Aminoff, M J; Ehsanullah, R S; Turner, P
Abstract : The uptake of tritiated dopamine and 5-hydroxytryptamine by platelets from 11 patients with Parkinsonism who were not receiving any medication, and from 11 control subjects matched for sex and for age within a decade was compared. No significant differences were found in the uptake of either amine. Our findings, therefore, provide no support for the belief that there is a generalised defect of dopamine systems in Parkinson's disease.